Pearls for opioid use in seriously ill patients. (3rd April 2019) - Kral, Lee; Ku, Jennifer; Kematick, Benjamin S.; Fudin, Jeffrey
Abstract: Opioids are often the foundation of pain management in seriously ill patients. Unfortunately, even experienced providers carry with them information that they consider "fact", when this information is not based on scientific evidence, but on "myth". Several topics were elicited based on common beliefs and misconceptions in clinical practice. These were identified via a survey of pharmacist pain and palliative care providers. Pearls from these topics were chosen that were based on evidence and would have the greatest bearing on clinical practice. The pearls address topics such as not using opioids as first-line analgesics for all types of pain, opioid-induced hyperalgesia, opioid risk management in cancer patients, use of buprenorphine in hospice and palliative care settings and use of naloxone in seriously ill patients. The pearls are supported by clinical evidence extracted from several references. They are intended to make readers give thought to opioid therapy which is strictly evidence-based, and not historical or anecdote-based. Practical recommendations are provided to give readers a starting point to base clinical decisions going forward. Readers may discover that "facts" they once learned about opioid use in seriously ill patients are actually "myths" that are a figment of the past.